Emerging Paradigms in Regenerative Medicine: Stem cell Therapies - Bhuvnesh, K. Sharma (Journal of Evolving Stem Cell Research, 2017)
Stem cell research is now emerging as most exciting and promising area of modern biomedical research which has enormous potential for easing suffering for many diseases such as Parkinson’s, Alzheimer’s, Diabetes,Cancer and many more. This is now recognized most promising alternate therapeutic choice for some of the diseases which currently have no other option of an effective therapy. The Stem cell therapy is now strengthened by cutting- edge technologies and rigorous standards of clinical research thus rapidly progressed from bench to the clinic.
Keywords: Stem cell therapy